Apropos of a Case: Focal and Segmental Glomerulosclerosis with a Normal Urine Examination - Palacios Guillén, Alaciel Melissa (2012)
The clinical presentation of focal and segmental glomerulosclerosis (FSGS) includes edema, an abnormal urine examination, and variably decreased kidney function. A twenty three year-old female patient, with a non-remarkable medical history developed during the last 18 months lower extremity, facial, and chest wall edema, and decreased urinary output that improved with the use of diuretics, but after two months she had a recurrence of her symptoms. Physical examination revealed the presence of eyelid and leg edema. Relevant laboratory tests showed normal creatinine values, creatinine clearance 61 mL/min, normal urinalysis, normal proteinuria; ANA, anti-DNA, hepatitis and HIV tests were reported as negative. C3 was also normal, as well as kidney ultrasonography. A kidney percutaneous biopsy was performed, which showed 8/20 affected glomeruli, and focal and segmental glomerulosclerosis.